2021
DOI: 10.1155/2021/9971765
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Risk Is Increased with a Sedentary Lifestyle during Aging in Mexican Women

Abstract: Oxidative stress (OS) increases during the human aging process, and the sedentary lifestyle could be a prooxidant factor. In this study, we determine the effect of sedentary lifestyle on OS during the aging process in Mexican women. A longitudinal study of two-year follow-up was carried out with 177 community-dwelling women (40-69 y) from Mexico City. We measured as OS markers plasma malondialdehyde, erythrocyte glutathione peroxidase (GPx) and superoxide dismutase (SOD), total plasma antioxidant status, uric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…(30) Sweating through exercise can enhance the excretion of heavy metals within the body, while research has demonstrated that a sedentary lifestyle can elevate the risk of oxidative stress. (31) Clinical trials focusing on exercise training have revealed a positive correlation between increased physical activity and elevated levels of GPX. (32) Furthermore, animal experiments have indicated that endurance training can induce alterations in the activities of antioxidant enzymes within the spleen, lymph nodes, and thymus, thereby in uencing the aerobic metabolism of these immune-related organs.…”
Section: Antioxidant Effect Of Physical Activitymentioning
confidence: 99%
“…(30) Sweating through exercise can enhance the excretion of heavy metals within the body, while research has demonstrated that a sedentary lifestyle can elevate the risk of oxidative stress. (31) Clinical trials focusing on exercise training have revealed a positive correlation between increased physical activity and elevated levels of GPX. (32) Furthermore, animal experiments have indicated that endurance training can induce alterations in the activities of antioxidant enzymes within the spleen, lymph nodes, and thymus, thereby in uencing the aerobic metabolism of these immune-related organs.…”
Section: Antioxidant Effect Of Physical Activitymentioning
confidence: 99%
“…83 NO/inflammation signaling cascade pathway may mediate several diseases, including lung squamous cell carcinoma, colon cancer, depression, and diabetes. [84][85][86][87] One category of nitric oxide synthase factors, endothelial nitric oxide synthase (eNOS), plays a significant role in managing NO function by stimulating NO synthesis. 88 Ischemia/reperfusion-induced acute kidney injury, ischemia/reperfusion-induced liver injury, hypertension, and steatohepatitis have been highlighted as associated disorders with the PPAR/eNOS axis.…”
Section: Cellular Mechanisms Relating Oxidative Stress and Cell Death...mentioning
confidence: 99%
“…19 Moreover, long exercise training, overtraining syndrome, and exhausting exercises increase ROS production. 86 In contrast, prolonged and low/moderate-intensity training ameliorates endogenous antioxidant status. Based on the evidence, physical activity could up-regulate mitogen-activated protein kinase (MAPK), and NF-κB induces several hub genes and proteins involved in the homeostasis, inflammation, and antioxidant/oxidative intracellular.…”
Section: • Lifestyle and Oxidative Stressmentioning
confidence: 99%
“…19 Moreover, long exercise training, overtraining syndrome, and exhausting exercises trigger oxidative stress pathways. 86 In contrast, prolonged and low/moderate-intensity training ameliorates endogenous antioxidant status. Based on the evidence, physical activity could up-regulate mitogen-activated protein kinase (MAPK), and NF-κB induces several hub genes and proteins involved in the homeostasis, inflammation, and antioxidant/oxidative intracellular.…”
Section: Non-coding Rnas and Oxidative Stress In The Management Of Ty...mentioning
confidence: 99%